2015
DOI: 10.1111/and.12499
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of udenafil citrate, piracetam and dexmedetomidine treatment on testicular torsion/detorsion-induced ischaemia/reperfusion injury in rats

Abstract: The aim of this study was to investigate the antioxidant properties of udenafil citrate (1.4 mg kg(-1) -2.8 mg kg(-1) ), dexmedetomidine 25 μg kg(-1) and piracetam 200 mg kg(-1) administered on ipsilateral/contralateral testes after ischaemia in a rat model of testicular torsion/detorsion (T/D) and define its protective effect histologically. Fifty-six Wistar albino rats were included and randomly assigned into 6 groups. No intervention was performed in control group (Group 1, n = 8) and in torsion/detorsion g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…It also shows beneficial effects on improving histopathological parameters caused by torsion. Other phosphodiesterase inhibitors, like trapidil and dipyridamole, decreased histological damage caused by testicular torsion (16)(17)(18). Since vitamin C is a potent antioxidant, it reduces the damage caused by testicular torsion.…”
Section: Discussionmentioning
confidence: 99%
“…It also shows beneficial effects on improving histopathological parameters caused by torsion. Other phosphodiesterase inhibitors, like trapidil and dipyridamole, decreased histological damage caused by testicular torsion (16)(17)(18). Since vitamin C is a potent antioxidant, it reduces the damage caused by testicular torsion.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of udenafil citrate, piracetam and dexmedetomidine in different doses was evaluated by Tuglu et al[90] and found that all these agents have antioxidant effects on I/R injury.…”
Section: Searchmentioning
confidence: 99%
“…Testicular torsion is the most common cause of urological emergency in young and adolescent males (Tuglu et al, 2016 ). Once diagnosed, clinical treatment should be adopted to restore blood flow to the testis within an appropriate time frame (Kim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%